Systematic analysis of integrated bioinformatics to identify upregulated THBS2 expression in colorectal cancer cells inhibiting tumour immunity through the HIF1A/Lactic Acid/GPR132 pathway - Ye Liu; Chunhui Jiang; Chunjie Xu; Lei Gu (Cancer Cell International, 2023)
Abstract Background THBS2, a member of the extracellular matrix glycoprotein family, can effectively inhibit tumour growth and angiogenesis. This study aimed to investigate the biological role of THBS2 in various types of cancers and the mechanisms underlying the malignant progression of colorectal cancer (CRC). Methods THBS2 expression in pan-cancer tissues and cell lines was assessed using the HPA, TISCH and CCLE databases. The CIBERSORT, ESTIMATE, TIMER, xCell and ssGSEA (implemented using the IOBR R package) algorithms were used to calculate the proportion of tumour-infiltrating immune cells based on the expression profile of THBS2 in TCGA-COAD cohort. The clusterprofiler R package was used to implement GO and KEGG pathway enrichm SNVs were compared between the high- and low-THBS2-expression groups using the maftools R package. Additionally, immunotherapy responses were compared between the high- and low-THBS2-expression groups based on immunophenoscores (IPSs). CT26 cells were engineered to overexpress THBS2 (CT26-THBS2) to investigate its regulatory effects on HIF1 and cellular metabolism. The conditioned medium from CT26-THBS2 cells was collected to examine its effect on the M2 polarisation of RAW264.7 macrophages. Subsequently, in vitro experiments were performed to validate the inhibitory effects of M2-polarised macrophages on T-cell proliferation and cytotoxicity. A CT26-THBS2 tumour-bearing mouse model was constructed to validate the impact of high THBS2 expression in tumour cells on the tumour microenvironment in vivo. Results THBS2 expression was upregulated in a majority of tumours, including COAD, and was positively associated with ESTIMATEScore, ImmuneScore and StromalScore. Furthermore, THBS2 expression was positively associated with angiogenesis and epithelial–mesenchymal transition and negatively associated with DNA repair, cell cycle and DNA replication in most tumours. THBS2 expression was considerably associated with progression-free interval (PFI) and positively associated with MSI in COAD. THBS2 methylation levels were remarkably lower in COAD tissues than in healthy tissues. The high expression of THBS2 in CT26 cells remarkably promoted the nuclear translocation of HIF1 and consequently enhanced lactate metabolism in cells. In vitro and in vivo experiments revealed that lactate released by tumour cells promoted M2 polarisation of macrophages, leading to inhibition of T-cell proliferation and cytotoxicity. Conclusions THBS2 expression is associated with PFI, immune cell infiltration, immune regulation, cell death, cell migration, epithelial–mesenchymal transition, angiogenesis and genomic variations in COAD. THBS2 may serve as a biomarker for immunotherapy in COAD. Upregulated THBS2 expression in CRC cells inhibits anti-tumour immunity through the HIF1A/lactic acid/GPR132 pathway.